Evolução e determinantes de acesso ao seguro agrícola no estado do Rio Grande do Sul - Oliveira, Helena Silva (2024)
Rio Grande do Sul is one of the most important agricultural states, both in terms of planting and production and in terms of agricutural insurance, and has been little studied in recent years, especially since 2020, when it experienced several climatic storms that had an impact on crops. With this in mind, this study aimed to analyze the evolution in the use of the Rural Insurance Premium Subsidy Program (PSR) in Rio Grande do Sul between the 2016/2017 and 2022/2023 harvests and its access determinants. The state of Rio Grande do Sul was the focus of this research, considering its relevance in the global agricultural scenario. The time frame defined was between the 2016/2017 and 2022/2023 crop years, as there is a lack of research on rural insurance in the state in recent times. The method used was mixed, using quantitative techniques such as collecting secondary data on subsidies, premiums, the number of policies and their spatial distribution, and qualitative techniques through semi-structured interviews with rural producers, seeking to understand the motivators for adopting rural insurance. The study site chosen was the municipality of Marau, in Rio Grande do Sul, where the agricultural sector is very important and accounts for a considerable share of local revenue. The results showed that soya was the main crop insured in Rio Grande do Sul, followed by grapes. However, grapes are the crop with the highest percentage of total cultivated area insured, oscillating between 51% and 60% in the period analyzed. The predominance of insurance based on productivity is strong. Looking at the evolution of claims, the 2019/20 harvest reached the peak of impacted contracts, with 23.6% of the total insured. Drought was the main claim event, accounting for 51.69% of contracts in the period analyzed. Among the results found in the interviews, it was clear that the search for rural insurance had four motivating factors: i) Costing higher than the Proagro limit, a policy that is more widespread in the municipality of Marau/RS; ii) PSR offers more satisfactory coverage for the protection that is not required; iii) Guarantee of payment of expenses incurred with inputs and; iv) Guidance via a bank agency to guarantee financing for the area.